2017
DOI: 10.1016/j.ctim.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Music listening alleviates anxiety and physiological responses in patients receiving spinal anesthesia

Abstract: Listening to music while in the recovery room may decrease the level of anxiety in surgical patients receiving spinal anesthesia. The results of this study can serve as a reference for PACU nurses in utilizing music listening programs to achieve the goal of holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
13
0
8
Order By: Relevance
“…Previous studies that investigated the psychological effects of exposure to nature-derived stimuli via other senses have reported similar improvements in mood states [20,22,25,26,36,62]. Several previous studies on music therapy reported its positive effect on mood states, such as in reducing anxiety levels in surgical patients [63] or facilitating a positive change in calm–anxious, energetic–tired, and agreeable–hostile mood states of adults with neurological impairments [64]. The present study demonstrated that the forest sound provided psychological benefits of positive feelings and mood state improvement similar to the effects of music therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies that investigated the psychological effects of exposure to nature-derived stimuli via other senses have reported similar improvements in mood states [20,22,25,26,36,62]. Several previous studies on music therapy reported its positive effect on mood states, such as in reducing anxiety levels in surgical patients [63] or facilitating a positive change in calm–anxious, energetic–tired, and agreeable–hostile mood states of adults with neurological impairments [64]. The present study demonstrated that the forest sound provided psychological benefits of positive feelings and mood state improvement similar to the effects of music therapy.…”
Section: Discussionmentioning
confidence: 89%
“…A pressão arterial foi avaliada de formas diferentes nos estudos. Dos artigos selecionados, um utilizou esfigmomanômetro e estetoscópio 17 , um, monitor de pressão digital 18,19 e três, monitor multiparamétrico [20][21][22] . Nos demais estudos não foram informados o recurso utilizado e a metodologia utilizada para mensuração.…”
Section: Resultsunclassified
“…O tempo de reprodução da música foi relatado em 10 dos 14 estudos que compuseram esta revisão, tendo como variação o intervalo de 10 a 60 minutos 12,17,19,20,22,[23][24][25][26][27] .…”
Section: Resultsunclassified
See 2 more Smart Citations